Hepatic stellate cells that coexpress LRAT and CRBP‐1 partially contribute to portal fibrogenesis in patients with human viral hepatitis. (24th July 2013) - Nagatsuma, Keisuke; Hano, Hiroshi; Murakami, Kazuhiro; Shindo, Daisuke; Matsumoto, Yoshihiro; Mitobe, Jimi; Tanaka, Ken; Saito, Masaya; Maehashi, Haruka; Owada, Mamiko; Ikegami, Masahiro; Tsubota, Akihito; et al.
Abstract Background & Aims Precisely what type of cells mainly contributes to portal fibrosis, especially in chronic viral hepatitis, such as hepatic stellate cells (HSCs) in the parenchyma or myofibroblasts in the portal area, still remains unclear. It is necessary to clarify the characteristics of cells that contribute to portal fibrosis in order to determine the mechanism of portal fibrogenesis and to develop a therapeutic target for portal fibrosis. This study was undertaken to examine whether LRAT+/CRBP‐1+ HSCs contribute to portal fibrosis on viral hepatitis. Methods Antibodies to lecithin:retinol acyltransferase (LRAT), cellular retinol‐binding protein‐1 (CRBP‐1) and widely ascertained antibodies to HSCs (alpha‐smooth muscle actin, neurotrophin‐3) and endothelial cells (CD31) were used for immunohistochemical studies to assess the distribution of cells that contribute to the development of portal fibrosis with the aid of fluorescence microscopy. A quantitative analysis of LRAT+/CRBP‐1+ HSCs was performed. Results The number of LRAT+/CRBP‐1+ HSCs was increased in fibrotic liver in comparison with normal liver in the portal area and fibrous septa. The number of double positive cells was less than 20% of all cells/field in maximum. Conclusion This study provides evidence that functional HSCs coexpressing both LRAT and CRBP‐1 that continue to maintain the ability to store vitamin A contribute in part to the development of portal fibrogenesis in addition to parenchymal fibrogenesis in patients with viral hepatitis.